TRANSFORMASI PEMBELAJARAN SAINS MELALUI GAME EDUKATIF “MAGNETIC CHALLENGE” DENGAN CONSTRUCT 2 - Putri, Nabila Amelia Kurnia; Nuriyah, Zidah Chotamy; Moryati, Yulisna; Nadzifah Salsabila; Aura Maharani Cahya Krisanti; Laili, Ummiy Fauziyah; Dewi, Ardiana Fatma (Tadris IPA Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This research develops the educational game Magnetic Challenge based on Construct 2 as a medium for learning magnetism. Using a qualitative descriptive method, the research focuses on needs analysis, media usage, and user feedback. The results show that this game is effective in helping visualize abstract concepts, increasing learning motivation, and deepening student understanding, although there are constraints regarding accessibility, audio, and flexibility of learning styles. Overall, this media is worth using as an innovative and enjoyable alternative for science learning for junior high school students.